Frontier Sumatra [videorecording (DVD)] - Barlow, Dilly (Dreamscape Media, 2023)
The documentary tells the incredible story of Restorasi Ekosistem Riau (RER), a ground-breaking rainforest conservation project in the Kampar Peninsula of Sumatra.